2005
DOI: 10.1210/jc.2004-1861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hormone Levels in Nipple Aspirate Fluid of Pre- and Postmenopausal Women: Effect of Oral Contraceptives and Hormone Replacement

Abstract: The effects of ovarian suppression by oral contraceptives as well as hormone replacement therapy were studied on hormone levels and on products of hormone action in nipple aspirate fluid (NAF) from breasts of pre- and postmenopausal women. Multiple samples per subject revealed high consistency (intraclass correlation coefficients) for all products measured. Compared with premenopausal women, NAF progesterone was much lower in postmenopausal women, but NAF androstenedione, dehydroepiandrosterone, and dehydroepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
31
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 28 publications
10
31
2
Order By: Relevance
“…When results in the present study are compared with our previous publications, it is true that estradiol concentrations in NAF have been consistently, but not significantly, lower in postmenopausal women than in premenopausal women. The number of postmenopausal subjects in our 2010 and 2004 publications was 18 in each (1,2). The higher postmenopausal NAF estradiol concentrations in the present study (3), although unexpected, can be attributed to chance when the sample size is small, as it was here, with 8 NAF-yielding postmenopausal subjects in the soy group.…”
supporting
confidence: 43%
“…When results in the present study are compared with our previous publications, it is true that estradiol concentrations in NAF have been consistently, but not significantly, lower in postmenopausal women than in premenopausal women. The number of postmenopausal subjects in our 2010 and 2004 publications was 18 in each (1,2). The higher postmenopausal NAF estradiol concentrations in the present study (3), although unexpected, can be attributed to chance when the sample size is small, as it was here, with 8 NAF-yielding postmenopausal subjects in the soy group.…”
supporting
confidence: 43%
“…Several studies have attempted to link NAF secretor status with breast cancer risk, but with mixed results (16,20). This is not surprising based on our observations that some of the reproductive factors associated with being secretors increase whereas others decrease the risk for breast cancer.…”
Section: Discussionmentioning
confidence: 80%
“…One possibility is that, even in premenopausal women, local biosynthesis of estrogens in the breast contributes significantly to the levels in the breast. There is good evidence of local biosynthesis of estrogens in breast tissue of postmenopausal women: a number of studies have shown that the steroid precursors required for estradiol synthesis are present in breast tissue (6,7), and high estrogen concentrations exist in NAF (8) and breast tissue (4)(5)(6)9) of postmenopausal women in the presence of dramatically lower concentrations of estrogens in plasma.…”
Section: Introductionmentioning
confidence: 99%